Die Identität von Ptychoptera paludosa coerulea Strobl, 1898 (Diptera: Ptychopteridae). - Zwick, Peter (Contributions to Entomology = Beiträge zur Entomologie, 1984)
The distniction of unicoloured dark Ptychoptera-female of the subgenus Paratychoptera is discussed. Ptychoptera paludosa coerulea Strobl, 1898, is recognized as a synonym of P. lacustris Meigen, 1830, on the basis of the holotype. Nomenclatural Acts coerulea Strobl, 1898 (Ptychoptera paludosa), syn. n. of Ptychoptera lacustris Meigen, 1830